Respuesta :

Answer:

5x +17

Step-by-step explanation:

Simplify step by step:

2( x+7 ) +3 ( x+1 )

We'll distribute:

= ( 2 ) ( x )  +  ( 2 ) ( 7 ) + ( 3 ) ( x ) + ( 3 ) ( 1 )

= 2x + 14  + 3x + 3

We'll Combine Like Terms:

= 2x + 14 + 3x + 3

= ( 2x + 3x ) + ( 14 + 3 )

= 5x + 17 Answer!

Answer:

Step by step Explanation:

2(x+7) +3(x+1)

Open the brackets (multiply outside number by the numbers and letters inside the brackets)

2x + 14 + 3x+ 3

Collect like terms (collect ones that look alike in one side )

2x + 3x + 14 + 3

Add the like terms (add the ones that look alike)

= 5x + 17 (Answer)

I hope you understand it, it's really simple just work step by step.

Good luck ✅.